2015
DOI: 10.1002/acp.3173
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness Evidence Obtained with the Self‐Administered Interview© Is Unaffected by Stress

Abstract: Please check the document version of this publication: • A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
2
21
1
1
Order By: Relevance
“…The SAI data were collected to investigate the possible beneficial value of retrieval support (as provided by the SAI) under varying levels of stress on immediate recall (i.e., no delay). These data are reported elsewhere (Krix et al, ). We hypothesized that the long time interval between completing these forms and performing the identification tasks (6–8 days) makes it unlikely that the recall task had an impact on identification performance.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The SAI data were collected to investigate the possible beneficial value of retrieval support (as provided by the SAI) under varying levels of stress on immediate recall (i.e., no delay). These data are reported elsewhere (Krix et al, ). We hypothesized that the long time interval between completing these forms and performing the identification tasks (6–8 days) makes it unlikely that the recall task had an impact on identification performance.…”
Section: Methodssupporting
confidence: 76%
“…Specifically, research in neurobiology has shown more pronounced positive effects of elevated levels of the stress hormone cortisol on recall than on recognition (Het et al, ). While analyses of the recall data collected in the current study also showed no effect of stress (Krix et al, ), this result cannot speak to the effect of stress on recall, because the recall and encoding phases followed closely on each other. Another explanatory account refers to the level of stress that can be induced in the laboratory.…”
Section: Discussioncontrasting
confidence: 50%
“…This might have led to differences in recall performance between the conditions . However, a recent study showed that stress does not influence recall performance when using the SAI as the recall tool (Krix et al, ). These findings suggest that emotional impact is perhaps not an alternative explanation for the difference found in accuracy results between the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that the quantity of correct information reported in an initial SAI © is higher than in other reporting formats such as free recall (e.g., Gabbert et al, 2009;Gawrylowicz et al, 2014a;Krix et al, 2016). Further research has probed the boundary conditions of this effect, showing, for example, that the magnitude of the SAI © benefit on correct details is reduced if the SAI © is administered following a delay of 24 hours or more (Mackay & Paterson, 2015;, or if attention was divided during encoding (Krix et al, 2014).…”
mentioning
confidence: 99%
“…Further research has probed the boundary conditions of this effect, showing, for example, that the magnitude of the SAI © benefit on correct details is reduced if the SAI © is administered following a delay of 24 hours or more (Mackay & Paterson, 2015;, or if attention was divided during encoding (Krix et al, 2014). There is some evidence, however, that the SAI © produces similar benefits under high and low stress (Gittins et al, 2015;Krix et al, 2016). The vast majority of research with the SAI © has focused on neurotypical young and middle-aged adults, though some studies have investigated other populations such as older adults (Dando et al, 2020;Gawrylowicz et al, 2014b) and adults with Autism Spectrum Disorder (Maras et al 2014).…”
mentioning
confidence: 99%